Pelaksanaan Hubungan Sekolah dan Stake Holder di MI Inayatushshibyan II Banjarmasin - Hj. Noor Hilmah; Rahmah Apriliyana; Miftahul Jannah; Rita Apriani; Ruhana (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2023)
This research aims to find out how the relationship between schools and stakeholders in education is implemented at Madrasah Ibtidaiyah Inayatushshibyan II Banjarmasin. This research is qualitative in nature, where in this paper we can see the description of what is done by schools in implementing school stakeholder relationships and in education. The data collection technique in this research was an interview with the principal at Madrasah Ibtidaiyah Inayatushshibyan II Banjarmasin. The results of the research show that the relationship between schools and stakeholders at MI Inayatushshibyan II Banjarmasin includes (1) Implementation of school relationships with the community (2) Functions of school relationships with the community (3) Techniques for school relationships with stakeholders (4) evaluation of the implementation of school relationships with stakeholders holder The research results show that there is harmonious cooperation and is able to create a healthy learning environment, with good communication and evaluation techniques to create satisfactory results.